Interventions to Increase the Rate of Influenza and Pneumococcal Vaccination in Patients with Chronic Obstructive Pulmonary Disease: A Scoping Review - Samuel P. Trethewey; Neil Patel; Alice M. Turner (Medicina, 2019)
Background and Objective: Current evidence suggests that patients with chronic obstructive pulmonary disease (COPD) should receive influenza and pneumococcal vaccinations. Despite international guidelines recommending vaccination in patients with COPD, many patients remain unvaccinated. Reasons for vaccine non-acceptance are multifaceted and are likely to be influenced by multiple psychosocial factors and pre-existing health beliefs. The aim of this review was to identify interventions which have been shown to effectively increase vaccination rates in patients with COPD. Materials and Methods: A structured search of PubMed returned 491 titles. Following title and abstract screening, seven full-text articles reporting on 6 unique interventional studies were extracted for narrative synthesis. A variety of interventions were investigated which, for the purposes of this review, were grouped into patient-focussed, clinician-focussed and mixed interventions. Results: Three papers reported findings from clinical trials (2 unique studies) and 4 papers reported findings from before-after studies. Two studies were conducted in the primary care setting, the remaining studies were conducted in secondary and tertiary care. Most studies reported both influenza and pneumococcal vaccination rates. These studies suggest that multimodal interventions, which target multiple aspects of evidence-based care and use both patient-focussed and clinician-focussed techniques, may have the greatest impact on vaccination rates in patients with COPD. Conclusions: Further, adequately powered, high quality studies are needed. It is crucial for individual institutions to monitor their own vaccination rates to determine if there is scope for performance improvement.